Physical activity of community-dwelling older adults living with mild cognitive impairment - Hopkins, Jane Adele (Curtin University, 2024)
This PhD aimed to enhance understanding of fall prevalence and risks for older adults with mild cognitive impairment. It linked with the Balance on the Brain Trial to investigate physical activity and sedentary behaviours and to determine if there was an association with cognitive domain skills. It also explored the effects of a balance intervention from the perspective of the participants with mild cognitive impairment, physiotherapists delivering the intervention, and the main informal support person.